PENGARUH ISLAMIC SERVICE QUALITY DAN ISLAMIC BRANDING TERHADAP KEPUASAN NASABAH BANK SYARIAH INDONESIA - Prabowo, Catur; Pelupessy, Henri; Fahlefi, Diva Riza; Harminingtas, Rudika (STIE PENA, 2025)
This study aims to determine the effect of Islamic Service Quality and Islamic Branding on Customer Satisfaction of Bank Syariah Indonesia in Semarang City. The population of this study is Bank Syariah Indonesia customers in Semarang City whose number is not known for sure (infinity population), so the sampling technique uses a simple random sampling method and is calculated using the roscoe formula with a 10% error rate. A sample of 97 Bank Syariah Indonesia customers in Semarang City was obtained. The data collection technique used a questionnaire and was analyzed using a multiple linear regression analysis approach. The results of this study indicate that partially Islamic Service Quality has a significant positive effect on Customer Satisfaction and Islamic Branding has a significant positive effect on Customer Satisfaction. While simultaneously Islamic Service Quality and Islamic Branding have a significant effect on Customer Satisfaction with a regression coefficient of 40.3%. Suggestions for Bank Syariah Indonesia are expected to improve the quality of Islamic services (Islamic Service Quality) and strengthen Islamic Branding to increase Customer Satisfaction. Suggestions for further researchers are expected to add other factors that influence customer satisfaction and expand the research object so that it can provide a more comprehensive insight into the factors that influence customer satisfaction in the context of Islamic banking.